(3MGTjI Ydi GdbUjOI GdYjfjI GdQhMjI dGHf SjfGs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3hHYO agPg MGTjI GdbUjOI GdefShHI Edi GdTjN GdQFjS CHj Ydi Hf SjfG QMeg Gddg s
(3BNQgG (B:s
(3hEf cGf GdKGfi ade bWYJ GdJYdjb Yf GdHOf HOhf GdceGd s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdadSaI hGdefWbs